Korelasi Penerapan Strategi Pembelajaran PQ4R dengan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti pada Siswa Kelas VIII SMP Katolik Siti Fatima Manado - Paulus Joseph Mentang (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2025)
This study aims to find out how the implementation of the PQ4R learning strategy in class VIII in the subjects of Catholic Religious Education and Character Education at Siti Fatima Catholic Middle School Manado, and a description of the learning outcomes of class VIII students in the subjects of Catholic Religious Education and Character Education at Siti Fatima Catholic Middle School. Manado and to find out whether there is a correlation between the implementation of the PQ4R learning strategy and the learning outcomes of Catholic Religious Education and Budi Pekerti for class VIII students at the Siti Fatima Catholic Junior High School Manado. The method used in this research is quantitative research with descriptive and correlational approaches. The research sample was the entire population taken from all students of class VIII, totaling 31 people at Siti Fatima Catholic Middle School Manado. The instrument trial was conducted on 31 students of class VIII. Test the validity of the instrument using the product moment correlation and reliability testing using the coefficient formula for the variable implementation of the PQ4R learning strategy and using the Cronbach Alpha value for the variable PAK and Budi Pekerti learning outcomes. The results of this study indicate that the students using the PQ4R learning strategy are in the very good category with an average score of 75.68 on a scale of 20-80 and the PAK and Budi Pekerti learning outcomes in this even mid-semester exam, the students get very good results. high with an average score of 98.71 on a scale of 0-100 and based on the product moment correlation results there is a strong correlation between the implementation of the PQ4R learning strategy and the learning outcomes of PAK and Budi Pekerti Class VIII students of Siti Fatima Catholic Middle School Manado of 0.712 with a significant value of 0.000 .